The impact of tax avoidance on the value of listed firms in Vietnam - Nguyen Minh Hai; Pham Tuan Anh; Xiao-Guang Yue; Nguyen Hoang Phi Nam (Cogent Business & Management, 2021)
The study aims to examine the impact of tax avoidance on the value of listed firms in Vietnam. Using a sample of 209 non-financial businesses listed on the Ho Chi Minh Stock Exchange (HOSE) in Vietnam for the period 2010-2018 and the Panel-Corrected Standard Errors (PCSE) to overcome the model's errors, we show that tax avoidance has a negative impact on the value of businesses at a 10% significance level. In addition, other variables, such as foreign ownership, investment, return on assets, leverage, the growth rate, firm size, sales index, and age of the firm, have a positive impact on firm value. In addition, variables such as state ownership and total accruals have a negative impact on firm value, and most of them are highly robust. However, firm size and the firm growth rate are not statistically significant in the study.
Keywords: 650; firm value; HOSE; PCSE; tax avoidance